A vascular endothelial growth factor A genetic variant is associated with improved ventricular function and transplant-free survival after surgery for non-syndromic CHD. (20th September 2017) - Mavroudis, Constantine D.; Seung Kim, Daniel; Burnham, Nancy; Morss, Alexandra H.; Kim, Jerry H.; Burt, Amber A.; Crosslin, David R.; McDonald-McGinn, Donna M.; Zackai, Elaine H.; Cohen, Meryl S.; Nicolson, Susan C.; Spray, Thomas L.; et al.
Abstract: Background: We have previously shown that the minor alleles of vascular endothelial growth factor A (VEGFA ) single-nucleotide polymorphism rs833069 and superoxide dismutase 2 (SOD2) single-nucleotide polymorphism rs2758331 are both associated with improved transplant-free survival after surgery for CHD in infants, but the underlying mechanisms are unknown. We hypothesised that one or both of these minor alleles are associated with better systemic ventricular function, resulting in improved survival. Methods: This study is a follow-up analysis of 422 non-syndromic CHD patients who underwent neonatal cardiac surgery with cardiopulmonary bypass. Echocardiographic reports were reviewed. Systemic ventricular function was subjectively categorised as normal, or as mildly, moderately, or severely depressed. The change in function was calculated as the change from the preoperative study to the last available study. Stepwise linear regression, adjusting for covariates, was performed for the outcome of change in ventricular function. Model comparison was performed using Akaike's information criterion. Only variables that improved the model prediction of change in systemic ventricular function were retained in the final model. Results: Genetic and echocardiographic data were available for 335/422 subjects (79%). Of them, 33 (9.9%) developed worse systemic ventricular function during a mean follow-up period of 13.5 years. After covariate adjustment, the presence of the VEGFA minor allele was associated with preserved ventricular function (p=0.011). Conclusions: These data support the hypothesis that the mechanism by which the VEGFA single-nucleotide polymorphism rs833069 minor allele improves survival may be the preservation of ventricular function. Further studies are needed to validate this genotype–phenotype association and to determine whether this mechanism is related to increased vascular endothelial growth factor production.